Life and Death of Termite Colonies, a Decades-Long Age Demography Perspective - Chouvenc, Thomas; Ban, Paul M.; Su, Nan-Yao (Frontiers in Ecology and Evolution, 2022)
A eusocial insect colony represents a complex biological entity that must ensure degrees of perennity once it reaches maturity (production of dispersing imagoes over many successive years) to optimize its reproductive success. It is known that a subterranean termite colony invests differentially in different castes over time and adjusts colony functions depending on colony internal and external conditions over many years of activity. However, the current study demonstrates that Coptotermes formosanus Shiraki field mature colonies go through dramatic demographic changes and breeding structure shifts, even many years after they have reached reproductive success. By analyzing the changes in age demography of C. formosanus colonies from four field sites, we here provide a new perspective on how a colony may function over decades, which reveals that each colony demographic trajectory is unique. In a way, throughout its life, a termite colony displays its own “demographic individuality” that drives its growth, its foraging ability, its competitiveness, its age demography, its senescence and ultimately its death. This study is therefore a narrated story of the life -and death- of different C. formosanus field colonies over decades of observation.